Best Answer

Where is y in this equation? 2x-3=9. First, you add 2 to both sides, and you get 2x=12. Divide both sides by 2;

so, x=6.

Q: Solve 2x-3 equals 9 for y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

y - 4 = 9 y - 4 + 4 = 9 + 4 y = 13

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

3/Y+7\Y=9 =>Y=10\9

9x + y = 22to solve for x-subtracy y from both sides --> 9x = 22 - ydivide by 9 on both sides --> x = (22/9) - (y/9)to solve for y - subtract 9x from both sides --> y = 22 - 9x

Related questions

3x-y=9 y=3x-9

y - 4 = 9 y - 4 + 4 = 9 + 4 y = 13

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

3/Y+7\Y=9 =>Y=10\9

Set x=0, solve for y, which is the y intercept: 0 - 3y = 9 --> y = -3. Set y=0 and solve for x = 9 for x-intercept.

9x + y = 22to solve for x-subtracy y from both sides --> 9x = 22 - ydivide by 9 on both sides --> x = (22/9) - (y/9)to solve for y - subtract 9x from both sides --> y = 22 - 9x

-9

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

x = -1.2, y = -3

y=4x-8y=2x+10Substitute (4x-8) for y in the second equation and solve for x:4x-8=2x+102x=18x=9Now solve for y:y=4(9)-8=28(9,28)

-y + y equals 0.